Meningkatkan Kepedulian Lingkungan Melalui Sosialisasi Pemilahan Sampah Pada Generasi Muda - Wibowo, Handy; Izzudin, Muhammad Aznil; Ibrahim, Muhammad Misbakhul Munir; Dewi, Siska Arini Kusuma; Fadilatul Naza, Mila Fadilatul; Yanuarika, Tantia Putri; Hiyatul, Dwi Fit; Pratiwi, Clara Sinta (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Waste management remains a critical environmental issue, particularly in rural areas such as Tanggulkundung Village, Tulungagung Regency, which lacks adequate infrastructure and ecological awareness. This community service activity aims to raise environmental awareness among the younger generation through a waste-sorting awareness campaign using the Asset- Based Community Development (ABCD) approach, which focuses on strengthening local assets, particularly elementary school students as agents of change. The implementation method consisted of four stages: asset identification, educational material planning, interactive outreach to students in grades 1–6 at SDN 1 and SDN 2 Tanggulkundung, and evaluation of the program outcomes. The results showed active participation from 54 students with a significant increase in knowledge and attitudes regarding waste sorting. Teachers and school principals reported behavioral changes among students and expressed support for sustaining the initiative. The discussion emphasizes that age-appropriate educational methods and institutional support are key to the success of the ABCD approach.